Protective Effects of Alpha-Lipoic Acid on Methotrexate-Induced Oxidative Lung Injury in Rats - (:unkn) unknown (TAYLOR & FRANCIS INC, 2018)
Objective: Oxidative stress is one of the major causes of methotrexate induced lung injury (MILI). Alpha-lipoic acid (ALA), which occurs naturally in human food, has antioxidative and anti-inflammatory activities. The aim of this study was to research the potential protective role of ALA on MILI in rats. Methods: Twenty one rats were randomly subdivided into three groups: control (group I), methotrexate (MTX) treated (group II), and MTX+ALA treated (group III). Lung injury was performed with a single dose of MTX (20mg/kg) to groups 2 and 3. On the sixth day, animals in all groups were sacrificed by decapitation and lung tissue and blood samples were removed for histological examination and also measurement the levels of interleukin-1-beta (IL-1), malondialdehyde (MDA), glutathione (GSH), tumour necrosis factor-alpha (TNF-), myeloperoxidase (MPO), and sodium potassium-adenosine triphosphatase (Na+/K+ATPase). Results: In MTX group tissue GSH, Na+/K+ATPase activities were lower, tissue MDA, MPO and plasma IL-1?, TNF-? were significantly higher than the other groups. Histopathological examination showed that lung injury was less severe in group 2 according to group 3. Conclusions: Oxidative damage of MTX in rat lung is partially reduced when combined with ALA.
Keywords: lung; oxidative stress; alpha-lipoic acid; methotrexate; rat; injury; MYELOPEROXIDASE ACTIVITY; MOLECULAR-MECHANISMS; RHEUMATOID-ARTHRITIS; LIPID-PEROXIDATION; DOSE METHOTREXATE; DAMAGE; INFLAMMATION; TOXICITY; STRESS